Acute Acquired Concomitant Esotropia: Clinical features, Classification, and Etiology. Issue 51 (December 2015) - Chen, Jingchang; Deng, Daming; Sun, Yuan; Shen, Tao; Cao, Guobin; Yan, Jianhua; Chen, Qiwen; Ye, Xuelian
Abstract : Abstract: Acute acquired concomitant esotropia (AACE) is a rare, distinct subtype of esotropia. The purpose of this retrospective study was to describe the clinical characteristics and discuss the classification and etiology of AACE. Charts from 47 patients with AACE referred to our institute between October 2010 and November 2014 were reviewed. All participants underwent a complete medical history, ophthalmologic and orthoptic examinations, and brain and orbital imaging. Mean age at onset was 26.6 ± 12.2 years. Of the 18 cases with deviations ≤ 20 PD, 16 presented with diplopia at distance and fusion at near vision at the onset of deviation; differences between distance and near deviations were < 8 PD; all cases except one were treated with prism and diplopia resolved. Of the 29 cases with deviations > 20 PD, 5 were mild hypermetropic with age at onset between 5 and 19 years, 16 were myopic, and 8 were emmetropic with age at onset > 12 years; 24 were surgically treated and 5 cases remained under observation; all 24 cases achieved normal retinal correspondence or fusion or stereopsis on postoperative day 1 in synoptophore; in 23 cases diplopia or visual confusion resolved postoperatively. Of the 47 cases, brain and orbital imaging in 2 cases revealed a tumor in the cerebellopontine angle and 1 case involved spinocerebellar ataxia as revealed by genetic testing. AACE in this study was characterized by a sudden onset of concomitant nonaccommodative esotropia with diplopia or visual confusion at 5 years of age or older and the potential for normal binocular vision. We suggest that AACE can be divided into 2 subgroups consisting of patients with relatively small versus large angle deviations. Coexisting or underlying neurological diseases were infrequent in AACE.